IDENTIFIKASI RAYAP BENUANG BINI (Octomeles sumatrana Miq) DI KHDTK HAURBENTES - Yeni Nuraeni; Illa Anggraeni; Rina Bogidarmanti (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Benuang Bini Plant is one of alternative plant as raw material for the pulp industry. This species hasnâ€™t been develoved extensively in the form forest plantation in Indonesia. Development activities in the form of pilot project has been developed by the Forestry Reseach and Development in KHDTK Haurbentes, West Java. In the benuang bini plant development, have various constraints such as pest and diseases attack. One of the pest that attack benuang bini plant in KHDTK Haurbentes is termite. The study was conducted in October 2014 in KHDTK Haurbentes, aims to identify the species of termites, knowing the percentage and observation of symptoms of termite attack. The study was conducted by survey method, sampling termites and termite species identiï€cation in the laboratory. The identiï€cation result termites that attack benuang bini is Microtermes sp. famili Termitidae. The percentage of attack are relatively low at 0,8 %. Termite control done by eradication and extermination from planting area.